Facility inspection using UAVs: a case study in the University of Georgia campus. Issue 21 (2nd November 2018) - Moore, Julian; Tadinada, Harshitha; Kirsche, Kevin; Perry, Jason; Remen, Fred; Tse, Zion Tsz Ho
ABSTRACT: Facility inspections are an essential factor to maintaining the physical integrity of a building for several years. If inspections and follow up maintenance are only performed when reported, a significant portion of building damages will go unnoticed until the interior of the building is affected. Using unmanned aerial vehicles (UAV) for facility inspections presents a preventative approach to current inspection processes. The proposed technology is based on low-cost, high performance unmanned aerial vehicles integrated with modern sensing technologies for building and infrastructure inspections. The UAV prototype is based on highly developed consumer drone modified with thermal imaging capabilities to maximize visibility for a diverse range of damages. The focus of this case study is the inspection of potential damages associated with water, heat, and the Heating, Ventilation, and Air Conditioning (HVAC) system. Inspections with the assistance of UAVs can visualize areas of a building's exterior where it is difficult to access or poses a safety risk to the inspector. This work provides a simplistic and cost-effective method to perform spot inspections of facilities. Results confirm that early detection of potential compromising utilities is possible with UAVs, which could prolong the life of equipment and facilities, effectively making the campus more sustainable.